Electrospun poly(lactic acid) (PLA): poly(ε-caprolactone) (PCL)/halloysite nanotube (HNT) composite fibers: Synthesis and characterization - Haroosh, Hazim; Dong, Yu (Elsevier, 2015)
The incorporation of nanoparticles into polymer nanocomposites via electrospinning offers an effective approach to tailor composite properties and fabricate nonwoven fibrous structures. This chapter describes a general fabrication-characterization route of electrospinning poly(lactic acid) (PLA):poly(ε-caprolactone) (PCL)/halloysite nanotube (HNT) composite fibers. High molecular weight PCL (9 wt%/v and 15 wt%/v)- and PLA (fixed at 8 wt%/v)-blend solutions were prepared with unmodified HNTs and HNTs modified with 3-aminopropyltriethoxysilane. HNTs were also incorporated into PLA:low molecular weight PCL (15 wt%/v) using different solvents (dichloromethane:N, N, dimethylformamide and chloroform:methanol cosolvents) and blend ratios.